(untitled) (Medical Forum Monthly, 2026)
Objective: To evaluate the impact of high-fructose dietary intake on hepatic enzyme regulation, insulin resistance, and metabolic profiles in young adults, and to determine correlations between fructose consumption and key metabolic indicators. Study Design: Prospective, comparative studyPlace and Duration of Study: This study was conducted at the Poonch Medical College Rawalakot, from July 2024 to June 2025. Methods: This prospective, comparative study include 210 young adults aged 18–30 years. Results: High-fructose consumers demonstrated significantly higher BMI (27.4 ± 4.3 kg/m2), waist circumference (88.7 ± 10.1 cm), and daily caloric intake (2450 ± 430 kcal) than low-fructose individuals. Hepatic enzymes including ALT (50.7 ± 15.1 vs. 34.9 ± 10.2 U/L), AST (41.8 ± 12.1 vs. 31.0 ± 8.9 U/L), ALP, and GGT wereelevated in the high-fructose group (all p < 0.001). Hepatic steatosis prevalence was nearly double (39% vs. 20%). Insulin resistance markers were significantly worse, with higher fasting glucose (102.7 ± 11.1 mg/dL), fasting insulin (18.2 ± 7.1 μIU/mL), and HOMA-IR (4.65 ± 1.52 vs. 2.39 ± 0.96). Lipid abnormalities included higher triglycerides (189.4 ± 45.2 mg/dL), higher LDL, and lower HDL. Fructose intake strongly correlated with ALT (r = 0.62), HOMA-IR (r = 0.71), triglycerides (r = 0.58), and waist circumference (r = 0.49), all p < 0.001. Conclusion: High fructose intake is associated with significant hepatic stress, insulin resistance, dyslipidemia, and central adiposity in young adults. Early metabolic disruption underscores the need to reduce fructose-rich foods and beverages to prevent long-term metabolic disease.